PENGARUH EKSTRAK BATANG BROTOWALI (Tinospora crispa) TERHADAP KEMATIAN LARVA NYAMUK Aedes aegypti - Agustiani Dumeva; Syarifah Syarifah; Syahidah Fitriah (Biota, 2016)
Aedes aegypti mosquito, which acts as a vector in the spread of dengue disease. One of the effort to reduce thespread of dengue disease is using larvicides. Brotowali thought to have an effect as larvicides against Aedesaegypti larvae because they have the alkaloid compounds and tinokrisposid that can cause death in larvae. Thisstudy aims to determine the effect extract brotowali (Tinospora crispa) against Aedes aegypti larvae of death soas to provide information to the public that can be used as larvicidal brotowali. This research is an experimentwith a completely randomized design (CRD) with 4 treatments and 6 replicates. The samples used were thirdinstar larvae of Aedes aegypti with the treatment A0 (abate 500 ppm), A1 (500 ppm), A2 (750 ppm), and A3(1000 ppm). Observations dead larvae were carried out for 24 hours and 48 hours. The results showed thatwithin 24 hours at a concentration of 500 ppm on average larvae death reached 32.5%, the concentration of 750ppm 55.8%, a concentration of 1000 ppm to 70%, whereas within 48 hours at a concentration of 500 ppm onaverage larvae death reached 75%, 90.8% concentration of 750 ppm, a concentration of 1000 ppm to 100%.Based on analysis of variance (Ansira) showed that the extract brotowali (Tinospora crispa) gives a significantinfluence (p > 0.01) in the death of larvae of Aedes aegyti. Effective concentration to kill larvae of Aedes aegytinamely the concentration of 750 ppm.